A GENERAL VELOCITY PROFILE FOR A LAMINAR BOUNDARY LAYER OVER FLAT PLATE WITH ZERO INCIDENCE (Journal of Engineering, 2011)
A general velocity profile for a laminar flow over a flat plate with zero incidence is obtained by employing a new boundary condition to the other available boundary conditions. The general velocity profile is mathematically simple and nearest to the exact solution. Also other related values, boundary layer thickness, displacement thickness, momentum thickness and coefficient of friction are nearest to the exact solution compared with other corresponding values for other researchers.